Bandstop Filter Design for GSM Shielding Using Frequency Selective Surfaces - Umair Rafique; Syed Ahsan Ali; M. Tausif Afzal; Mudassar Abdin (Institute of Advanced Engineering and Science, 2012)
In this paper, the performance of bandstop Frequency Selective Surface (FSS) is presented which can be used to provide wireless security on airports and other sensitive places, where a mobile phone can be used to set-off an explosive device. It can also be used to block the mobile signals at the places of worship, hospitals and cinemas where the annoying voice of a mobile phone may irritate the masses. The FSS unit cell consists of two metallic square-loop elements printed on FR-4 substrate with different periodicities. The outer and inner square-loop elements are tuned to 900 MHz and 1800 MHz, respectively. It has a stable frequency response at oblique incidences for both perpendicular (TE) and parallel (TM) polarizations. Simulation results are presented to give an overview for the performance of proposed FSS design.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1820